2021
DOI: 10.3390/pharmaceutics13020240
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Mannans to Enhance the Potency of Liposome Nanoparticles for the Delivery of RNA Vaccines

Abstract: Recent approval of mRNA vaccines to combat COVID-19 have highlighted the potential of this platform. Lipid nanoparticles (LNP) is the delivery vehicle of choice for mRNA as they prevent its enzymatic degradation by encapsulation. We have recently shown that surface exposition of mannose, incorporated in LNPs as stable cholesterol-amine conjugate, enhances the potency of self-amplifying RNA (SAM) replicon vaccines through augmented uptake by antigen presenting cells (APCs). Here, we generated a new set of LNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…185,186 Mannose receptor-mediated targeting has already been studied for DNA and RNA delivery in antitumor immunotherapy, 187 in the formulation of an HIV DNA vaccine, 188 and also for the delivery of self-amplifying mRNA (SAM) vaccines. 143,189 Mannose-coated particles were obtained by modifying the zwitterionic lipid components, 188 polyethylene glycol (PEG), 190,191 via ester bonds with cholesterol 187 or via conjugation to cholesterol amine. 143 Although mannose is already sufficient to trigger the DC-SIGN receptor and favor uptake from DC, we have recently observed that balance between oligomannose length and amount of PEG used for liposome stabilization (see next paragraph) can be exploited to further enhance the immunogenicity of SAM vaccines.…”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…185,186 Mannose receptor-mediated targeting has already been studied for DNA and RNA delivery in antitumor immunotherapy, 187 in the formulation of an HIV DNA vaccine, 188 and also for the delivery of self-amplifying mRNA (SAM) vaccines. 143,189 Mannose-coated particles were obtained by modifying the zwitterionic lipid components, 188 polyethylene glycol (PEG), 190,191 via ester bonds with cholesterol 187 or via conjugation to cholesterol amine. 143 Although mannose is already sufficient to trigger the DC-SIGN receptor and favor uptake from DC, we have recently observed that balance between oligomannose length and amount of PEG used for liposome stabilization (see next paragraph) can be exploited to further enhance the immunogenicity of SAM vaccines.…”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%
“…143 Although mannose is already sufficient to trigger the DC-SIGN receptor and favor uptake from DC, we have recently observed that balance between oligomannose length and amount of PEG used for liposome stabilization (see next paragraph) can be exploited to further enhance the immunogenicity of SAM vaccines. 189 These mannosylated liposomes hold the promise to be suitable for the development of skin delivery systems. Wamhoff et al described the design of liposome formulations covered with a glycomimetic ligand for the lectin receptor Langerin, to selectively target Langerhans cells, for the development of novel vaccination strategies.…”
Section: Combinatorial Adjuvant Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ziller et al published results on how EPC/DOPC/DOTAP LPX could be further modified to achieve controlled-release effects [104]. Furthermore, similarly to that which Goswami et al [80,81] studied for LNPs, and as previously commented in Section 2.1.1, the development of mannosylation strategies through the incorporation of mannose-modified lipids has also been proposed for LPX for specific targeting to macrophages, achieving positive results in the induction of a stimulatory immune response upon mice vaccination [113,114].…”
Section: Lipoplexesmentioning
confidence: 93%
“…routes [80]. Authors further investigated how the length of this LNP-surface decoration may influence antibody response, observing that vaccine priming response was improved with a higher chain length [81].…”
Section: Unraveling Lnp Compositionmentioning
confidence: 99%